2023
DOI: 10.1186/s12885-022-10411-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of staging, treatment, and mortality in gastric, colorectal, and lung cancer among older adults with and without preexisting dementia: a Japanese multicentre cohort study

Abstract: Background Little is known about dementia’s impact on patterns of diagnosis, treatment, and outcomes in cancer patients. This study aimed to elucidate the differences in cancer staging, treatment, and mortality in older cancer patients with and without preexisting dementia. Methods Using cancer registry data and administrative data from 30 hospitals in Japan, this multicentre retrospective cohort study examined patients aged 65–99 years who were ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Firstly, research suggests that the lower risk of AD among cancer patients may be attributed to underdiagnosis of AD (Freedman et al, 2016). On the other hand, many AD patients, especially male patients, cannot undergo colonoscopy in a timely manner due to cognitive dysfunction, memory loss, and emotional issues, and may not be diagnosed until the disease is advanced or even until death (Yang et al, 2021;Lv et al, 2022;Morishima et al, 2023). Secondly, research has found that chemotherapy for cancer survivors can reduce the risk of AD, such as the multi-target kinase inhibitor regorafenib used to treat CRC that can inhibit the inflammatory response caused by microglia and treat AD (Han et al, 2020;Akushevich et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, research suggests that the lower risk of AD among cancer patients may be attributed to underdiagnosis of AD (Freedman et al, 2016). On the other hand, many AD patients, especially male patients, cannot undergo colonoscopy in a timely manner due to cognitive dysfunction, memory loss, and emotional issues, and may not be diagnosed until the disease is advanced or even until death (Yang et al, 2021;Lv et al, 2022;Morishima et al, 2023). Secondly, research has found that chemotherapy for cancer survivors can reduce the risk of AD, such as the multi-target kinase inhibitor regorafenib used to treat CRC that can inhibit the inflammatory response caused by microglia and treat AD (Han et al, 2020;Akushevich et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 18 By integrating the OCR and DPC data, we constructed the OCR-DPC database for research purposes. 19 The creation of the OCR-DPC database was a collaborative effort with the Council for Coordination of Designated Cancer Care Hospitals in Osaka. The data for this study were collected from 36 hospitals and involved more than 50% of patients with cancer in Osaka Prefecture.…”
Section: Methodsmentioning
confidence: 99%
“…This multicenter retrospective cohort study used registry data from the Osaka Cancer Registry (OCR) linked to administrative claims data; Information taken from the OCR included cancer diagnosis and survival status of patients residing in Osaka Prefecture, as well as age, sex, type of cancer, date of cancer diagnosis, last follow-up date, date of death, and stage of cancer (i.e., localized, regional to lymph nodes, regional by direct extension, distant) [ [16] , [17] , [18] ]. The administrative claims data were based on Japan's Diagnostic Procedure Combination (DPC) per diem payment system, which governs reimbursement from insurance organizations to acute-care hospitals.…”
Section: Methodsmentioning
confidence: 99%